Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Reputasi Lembaga di Pondok Pesantren Salaf Al-Maliki - Moh.Wildan Fahmi; Akhmad Fauzi Hamzah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the leadership strategies of the headmaster in enhancing institutional reputation at Pondok Pesantren Salaf Al-Maliki Pekalongan. The background of this research is based on existing challenges, including weak institutional exposure, suboptimal community participation, and a lack of structured institutional branding. This study employed a qualitative method with a case study approach through participatory observation, in-depth interviews, and documentation. The findings reveal that the headmaster applies a transformational and participatory leadership style by emphasizing the character development of teachers and students. The main strategies implemented include strengthening traditional educational methods such as sorogan, bandongan, and kitab kuning recitation without translations (kosongan), which foster close teacher-student relationships and reinforce the identity of classical Islamic scholarship (salafiyah). The headmaster also applies open and collaborative managerial communication with the kyai (spiritual leader), teachers, and the community, along with a value-based selection process for recruiting educators. The study concludes that a combination of value-based leadership, classical educational programs, and collaborative communication contributes positively to the institution's reputation, as reflected in increased public trust, teacher comfort, and student motivation. This study recommends strengthening value-based strategic leadership and preserving salafiyah educational traditions as key factors in the successful development of modern Islamic educational institutions.